Do actors’ incentives obstruct sector-wide long-term productivity in the design and production of bridges in Sweden? - Johan Lagerkvist; Petra Bosch-Sijtsema; Ola Lӕdre; Mats Karlsson; Peter Simonsson; Rasmus Rempling (Journal of Civil Engineering and Management)
An increase in productivity is necessary to reduce economic costs in bridge projects. Previous research indicates that construction productivity has decreased since the 1960s. A quantitative study was performed to find out how the incentives of the three major actors (client, contractor, and design engineer) could be obstacles to long-term productivity in the Swedish bridge construction industry. The study was performed as a self-completed questionnaire and received 151 responses. The results show that the contractors’ employees find profit in a single project more important than the company’s profit over time. Thus, the project´s incentives obstruct innovation and standardization, which could benefit future projects and thereby increase long-term productivity and the company’s profit over time. In contrast to contractors, design engineers and clients value company profit more than profit in a single project, and they value the quality of delivered products as the most important factor for increased long-term productivity.